High-frequency shock wave lithotripsy: stone comminution and evaluation of renal parenchyma injury in a porcine ex-vivo model: original article - Rassweiler-Seyfried, Marie-Claire; Mayer, Jürgen; Goldenstedt, Cedric; Storz, Rafael; Marlinghaus, Ernst; Heine, Gerold; Alken, Peter; Rassweiler, Jens (World journal of urology, 2023)
The electrohydraulic high-frequency shock wave (Storz Medical, Taegerwilen, Switzerland) is a new way to create small fragments with frequencies up to 100 Hertz (Hz). This study evaluated the efficacy and safety of this method in a stone and porcine model.
Online veröffentlicht: 7. Juni 2023
Gesehen am 23.07.2024